Prevalence of Cervical Rib in Western Nepal - Lalchan, Subita; Jwarchan, Bishnu; KC, subash; Gyawali, Merina (Nepalese Journal of Radiology, 2018)
Introduction: Cervical rib is usually asymptomatic. It is usually detected incidentally when radiograph is done for other reasons. Cervical rib has been found to be symptomatic in about 10% of cases. This study was carried out to evaluate the prevalence of cervical ribs and percentage of symptomatic patients among Nepalese population in western development region. Methods: Total of 3600 chest and cervical spine radiographs of patients done for various purposes in radiology department were evaluated for presence of cervical rib. Study was carried out during September 2013 to February 2014. Patients of 16 years and above were included in the study. History was also noted to see if patients with cervical rib were symptomatic. SPSS version 17 software was used in data analysis. Results: Prevalence of cervical ribs was found to be 1.1 % with higher rate in females. Among 39 patients with cervical rib; bilateral cervical ribs was seen in 46.2 %. Cervical rib was more common on right side, seen in 38.5 % of cases. It was seen on left side in 15.4 % of cases. Cervical rib was found to be symptomatic in 10.25 % of patients. Among them; two patients presented with pain in arm and other two presented with hard swelling in right cervical region. Conclusion: The cervical rib is common in our population. Patients with pain, numbness in arm and swelling in cervical region should be evaluated for cervical rib.